Mobile Gamification Applied to Employee Productivity in Companies: A Systematic Review - Miguel Angel Cardoso Miranda (UIKTEN, 2021)
The main goal of this article is to identify the use of gamified mobile applications and their impact on work productivity. We employ a systematic review of the literature to discover to what extent gamified mobile applications improve worker productivity within a company. The intent is to contribute to more profound understanding of learning contexts, methodologies, techniques and objectives with the application of mobile gamification. The literature emphasizes that mobile gamification can be used to enhance the learning process, improve performance and achieve worker objectives, especially in production and IT areas. To do this, an analysis is presented of the areas that use mobile gamification, the techniques used and the effects that are achieved with its application in companies. It seeks to close the knowledge gap by quantifying the gamification characteristics found in applications. Due to the paucity of studies on mobile gamification at work productivity, this work also points the way to new research.